THE ANTI-INFLAMMATORY TABLET FORMULATION OF COLEUS (PLECTRANTHUS SCUTELLARIODES) LEAVES EXTRACT USING KOLLICOAT®PROTECT COATING - MUSTARICHIE, RESMI; RAMDHANI, DANNI; SAPTARINI, NYI MEKAR (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study was to find the concentration of weight gain on the use of Kollicoat®Protect to produce coleus leaf extract film-coated tablets with good physical properties. Methods: Coleus extract was obtained by maceration using 70% ethanol. Tablet cores were prepared using the wet granulation method, then evaluated (uniformity of weight, size, hardness, friability, and disintegration time). Coated tablets were made in four variations of polymer weight gain, i.e. 5, 6, 7, and 8%. To determine the effect of the weight gain concentration of Kollicoat®Protect an evaluation of the coated tablets was carried out, i.e. the uniformity of weight, size, hardness, disintegration time, and physical appearance of the film-coated tablets. Results: The four variations (Film Coated Tablet, FCT 5, 6, 7, and 8%) in weight gain of film-coated tablets showed the physical appearance results per the applicable requirements. However, the physical observation test at room temperature showed the instability of the film-coated tablet. The qualitative analysis of thin-layer chromatography showed that the productive substances in the extracts, tablet cores, and film-coated tablets were still contained even though they had undergone several formulation stages. Conclusion: Film-coated tablets met the standards of the Indonesian Pharmacopoeia and the United States Pharmacopeia. After two weeks, there was slight instability in film-coated tablets at room temperature storage. The extract, tablet core, and film-coated tablet contain flavonoids.